PENGARUH POLA PEMBERIAN PAKAN TERNAK DENGAN PEMANFAATAN SAMPAH ORGANIK PASAR TERHADAP EFISIENSI BIAYA PETERNAKAN (STUDI KASUS :KELOMPOK TANI SUMBER MAKMUR, GUNUNG TEMBAK KOTA BALIKPAPAN) - Dewi Zannaria, Noneng; Pratiwi , Reno; Bayu K. , Ika; Inggar R. , Sekar; Boyo M., Galuh; Oktavia, Evi (Program Studi Manajemen Fakultas Ekonomi Universitas Balikpapan, 2024)
The generation of organic waste, especially organic waste, continues to increase along with the population growth rate of Balikpapan City as a buffer city for the IKN. One source of organic waste is organic waste from market activities, especially traditional markets. If not managed properly, it can increase the risk of environmental pollution and the spread of disease vectors. The alternative use of organic market waste as animal feed has been carried out by the Sumber Makmur Gunung Tembak Farmers Group, Balikpapan City. With the management of animal feed combined with organic market waste, it is able to reduce livestock operational costs, especially the cost of providing feed. The purpose of this study was to determine the difference between the use of organic market waste for animal feed compared to using fresh grass. The results obtained are that by utilizing organic market waste, the cost of providing animal feed can be reduced and farmers benefit more in terms of financing and providing feed,